Soil Health Dynamics in Urban Forests versus Wasteland Soils: A Physico-Chemical Perspective from Subtropical Region of Chhattisgarh, India - Kumar Satyam; Gunjan Patil; Abhishek Maitry (Journal of the Indian Society of Soil Science, 2026)
Urbanization and land degradation significantly influence soil physicochemical characteristics and nutrient dynamics in subtropical ecosystems. This study comparatively evaluated soil health in urban forest soils (UFS) and wasteland soils (WLS) of Bilaspur, Chhattisgarh, India, analyzing soil colour, texture, bulk density (BD), moisture content (MC), nitrogen (N), carbon (C), hydrogen (H), and sulfur (S). Urban forest soils were generally darker (dark brown to dark grey) with finer textures (silt loam to clay), whereas wastelands exhibited lighter colours and coarser textures. Bulk density ranged from 1.45–1.60 g cm-3 in UFS and 1.10–1.28 g cm-3 in UFS. Moisture content varied from 7.6–15.2% in WLS and 18.0–31.5% in UFS. Carbon and nitrogen ranged between 0.58–1.45% and 0.046–0.138% in WLS, compared to 1.05– 1.68% and 0.204–0.408% in UFS, respectively. Pearson correlation analysis showed significant negative relationships (p < 0.05) between BD and nutrient parameters, with stronger associations in urban forest soils (e.g., BD–C r ≈ –0.76). Moisture exhibited strong positive correlations with carbon and nitrogen (r ≈ 0.86), indicating tight nutrient–water coupling under forest cover. Wasteland soils displayed comparatively weaker inter-parameter associations and greater variability. Multivariate scatterplot matrix analysis further confirmed stronger structural coherence and biogeochemical integration in urban forest soils compared to wastelands. Overall, the findings highlight the regulatory role of vegetation cover in maintaining soil structural stability and nutrient interdependence in the subtropical urban ecosystem of Bilaspur. The study underscores the ecological importance of conserving and restoring urban forest patches to enhance soil health resilience in rapidly expanding cities of central India.